Pakistan’s Foreign Policy: Challenges and Opportunities - Mr. Muhammad Sarmad Zia (CISS Insight Journal, 2018)
A country’s foreign policy is the lens through which it sees the rest of the world. It is of crucial significance in correctly reflecting its ambitions, goals and apprehensions vis-à-vis its neighborhood as well as the regional and the international milieu. In order to maintain cordial and balanced relations in the international arena, states employ several different tactics and methods. In the course of achieving this, states face many hardships. In this paper, Pakistan’s foreign policy will be analyzed to lay out the challenges it is facing currently and also the opportunities that are present for Pakistan to explore. It is a well-known fact that Pakistan’s foreign policy has undergone changes several times over the last few decades. Both military dictators and democratic leaders have shaped the country’s foreign policy according to their governing styles, thought processes, political influences and their understanding of the country’s security imperatives. Meanwhile, the external factors such as evolving regional, geo-political and global environment have played an equally critical role in shaping the foreign policy of Pakistan in different eras. Pakistan’s foreign policy at any given time is a resultant of both these factors.